STRATEGIC FINANCIAL MANAGEMENT IN SMALL AND MEDIUM ENTERPRISES: A GLOBAL PERSPECTIVE THROUGH A SYSTEMATIC LITERATURE REVIEW - Nurussama Nurussama; Wahab (CV. Adiba Aisha Amira, 2024)
Strategic financial management in Small and Medium Enterprises (SMEs) refers to the process of planning, organising, directing, and controlling the financial resources of small and medium-sized enterprises to achieve the long-term goals of the organisation. The concept involves making sound financial decisions, efficient resource allocation, effective risk management, and optimisation of capital structure to enhance enterprise value and ensure business sustainability in a dynamic global context. This approach integrates financial aspects with the overall business strategy, considering both internal and external factors that affect the financial performance of SMEs. The results show that strategic financial management plays a crucial role in improving SMEs' performance and sustainability. The study revealed several common effective practices, including long-term financial planning, efficient working capital management, and diversification of funding sources. However, the implementation of these practices often needs to be adapted to the local context and specific characteristics of SMEs. Key challenges identified include limited access to financial resources, lack of expertise in strategic planning, and difficulty managing risks in a dynamic business environment. The study also highlights the importance of technological innovation and business model adaptation in SME financial management.